Incremental Prognostic Value of Pericoronary Adipose Tissue Thickness Measured Using Cardiac Magnetic Resonance Imaging After Revascularization in Patients With ST-Elevation Myocardial Infarction - Ma, Yue; Ma, Quanmei; Wang, Xiaonan; Yu, Tongtong; Dang, Yuxue; Shang, Jin; Li, Guangxiao; Hou, Yang (Frontiers in Cardiovascular Medicine, 2022)
Background and aims: Pericoronary adipose tissue (PCAT) reflect peri-coronary inflammation and is associated with coronary artery disease. We aimed to identified the association between local PCTA thickness using cardiac magnetic resonance (CMR) and prognosis of patients with ST elevation myocardial infarction (STEMI), and to investigate the incremental prognostic value of PCAT thickness in STEMI after reperfusion. Methods: A total of 245 patients with STEMI (mean age, 55.61±10.52 years) who underwent CMR imaging within 1 week of percutaneous coronary intervention therapy and 35 matched controls (mean age, 53.89±9.45 years) were enrolled. PCAT thickness indexed to body surface area at five locations, ventricular volume and function, infarct-related parameters, and global strain indices were evaluated using CMR. Associations between PCAT thickness index and 1-year major adverse cardiovascular events (MACE) after STEMI were calculated. Prognostic value of standard model based on features of clinical and CMR and updated model including PACT thickness index were further assessed. Results: Patients with MACE had a more significant increase in PCAT thickness index at superior interventricular groove (SIVGi) than patients without MACE. The SIVGi was significantly associated with left ventricular ejection fraction (LVEF), infarct size and global deformation. SIVGi>4.98 mm/m2 was an independent predictor of MACE (hazard ratio, 3.2; 95% confidence interval (CI) 1.6-6.38; p <0.001). The updated model significantly improved the power of prediction and had better discrimination ability than that of the standard model for predicting 1-year MACE (AUC=0.8 (95% CI: 0.74 to 0.87) vs. AUC=0.76 (95% CI: 0.68-0.83), P<0.05; cfNRI=0.38 (95% CI: 0.1-0.53, P=0.01); IDI=0.09 (95% CI:0.01-0.18, P=0.02)). Conclusions: This study demonstrated SIVGi as an independent predictor conferred incremental value over standard model based on clinical and CMR factors in 1-year MACE predictions for STEMI.